Transcriptome Analysis of Gene Expression Provides New Insights into the Effect of Mild Therapeutic Hypothermia on Primary Human Cortical Astrocytes Cultured under Hypoxia - Salman, Mootaz M.; Kitchen, Philip; Woodroofe, M. Nicola; Bill, Roslyn M.; Conner, Alex C.; Heath, Paul R.; Conner, Matthew T. (Frontiers in Cellular Neuroscience, 2017)
Hypothermia is increasingly used as a therapeutic measure against brain injury. However, the cellular mechanisms underpinning its actions are complex and not fully elucidated. Astrocytes are the most abundant cell type of the brain and as such are likely to play a critical role in the hypothermia effects. In this study, the transcriptional changes and protein expression profile were investigated in human primary cortical astrocytes cultured under hypoxic conditions for 6h, with and without a mild hypothermic intervention 2h post-insult hypoxia/hypothermia to mimic the in vivo treatment situation following traumatic brain injury (TBI) and/or stroke. Using human gene expression microarray, 411 differentially expressed genes were identified following hypothermic treatment of astrocytes following a 2-hour hypoxia insult. KEGG pathway analysis indicated that these genes were mainly enriched in the Wnt and p53 signalling pathways; which were inhibited following hypothermic intervention. The expression levels of 168 genes involved in Wnt signalling pathway were validated by quantitative real-time-PCR (qPCR). Among these genes, 10 were up-regulated and 32 were down-regulated with the remainder unchanged. Two of the differentially expressed genes (DEGs), p38 and JNK, were selected for validation at the protein level using cell based ELISA. The results indicated that the hypothermic intervention significantly down-regulated total protein levels of p38 and JNK. Moreover, hypothermia significantly up-regulated the phosphorylated (activated) forms of JNK, while downregulating phosphorylation of p38. Within the p53 signalling pathway, 35 human apoptosis-related proteins closely associated with Wnt signalling pathway were investigated using Proteome Profiling Array. The results indicated that hypothermic intervention significantly down-regulated 18 proteins, while upregulating one protein, survivin. Hypothermia is a complex intervention; this study provides the first detailed longitudinal comparison at the transcript and protein expression levels investigating the molecular effects of therapeutic hypothermic intervention following hypoxia on human primary cortical astrocytes. The identified genes and proteins could be targeted for detailed functional studies and may help develop new treatments for brain injury based on an in-depth mechanistic understanding of astrocytic response to hypoxia and/or hypothermia.